Biredox‐Ionic Anthraquinone‐Coupled Ethylviologen Composite Enables Reversible Multielectron Redox Chemistry for Li‐Organic Batteries. Issue 1 (29th October 2021) - Wang, Zhongju; Fan, Qianqian; Guo, Wei; Yang, Changchun; Fu, Yongzhu
Abstract: Organic compounds bearing redox‐active ionic pairs as electrode materials for high‐performance rechargeable batteries have gained growing attention owing to the properties of synthetic tunability, high theoretical capacity, and low solubility. Herein, an innovative biredox‐ionic composite, i.e., ethylviologen dianthraquinone‐2‐sulfonate (EV‐AQ2 ), affording multiple and reversible active sites as a cathode material in lithium‐organic batteries is reported. EV‐AQ2 exhibits a high initial capacity of 199.2 mAh g −1 at 0.1 C rate, which corresponds to the transfer of two electrons from one redox couple EV 2+ /EV 0 and four electrons from two redox‐active AQ − anions. It is notable that EV‐AQ2 shows remarkably improved cyclability compared to the precursors. The capacity retention is 89% and the Coulombic efficiency approaches 100% over 120 cycles at 0.5 C rate. The results offer evidence that AQ − into the EV 2+ scaffold with multiple redox sites are promising in developing high‐energy‐density organic rechargeable batteries. Abstract : A biredox ionic ethylviologen dianthraquinone‐2‐sulfonate (EV‐AQ2 ) consisting of both redox cations and anions is synthesized. EV‐AQ2 can undergo reversible multielectron redox reactions to improve their stability and theoretical capacity, which corresponds to two electrons from EV 2+ cations and four electrons from AQ − anions. This study illustrates an effective strategy to design new ionic organic compounds for Li‐organic batteries.